2008
DOI: 10.1007/s00415-008-0737-6
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal levels of IL-6, IL-11 and LIF in Alzheimer's disease and frontotemporal lobar degeneration

Abstract: Cerebrospinal fluid (CSF) levels of interleukin (IL)-6, IL-11 and leukaemia inhibitory factor (LIF) were evaluated in 43 patients with Alzheimer's disease (AD) and 24 patients with frontotemporal lobar degeneration (FTLD) as compared with 30 agematched controls (CON), and correlated with clinical and demographic data and with CSF biomarkers amyloid beta (A beta)42, total tau and tau phosphorylated at position 181 (P-tau). CSF IL-11 mean levels were significantly increased in AD and FTLD as compared with CON (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
60
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 35 publications
5
60
1
Order By: Relevance
“…1A, B). There was no statistically signifi cant difference in LXA 4 or RvD1 levels between DMSO and A ␤ 40 conditions (supplementary Fig. 2A, B).…”
Section: Lms Released By Pbmcsmentioning
confidence: 91%
See 3 more Smart Citations
“…1A, B). There was no statistically signifi cant difference in LXA 4 or RvD1 levels between DMSO and A ␤ 40 conditions (supplementary Fig. 2A, B).…”
Section: Lms Released By Pbmcsmentioning
confidence: 91%
“…LXA 4 and RvD1 levels. Upon A ␤ 40 exposure, the release of LXA 4 and RvD1 from PBMCs was reduced after 6 months in the placebo supplementation group compared with baseline, while in the n-3 FA supplementation group the levels remained similar to that observed at baseline ( Fig.…”
Section: Lms Released By Pbmcsmentioning
confidence: 97%
See 2 more Smart Citations
“…
In a recent study, Galimberti et al [2] reported a significant increase of IL-11 disease (AD n = 43) and frontotomporal lobar degeneration (FTLD n = 24) in patients with Alzheimer's disease in comparison to age-matched controls (n = 30). At the same time, IL-6 showed only a non-significant increase in demented subjects.
…”
mentioning
confidence: 97%